Black adolescents' support to the family and educational outcomes: Differences by household income. Issue 1 (11th August 2022) - Armstrong‐Carter, Emma
Abstract: Using a strengths‐based approach, this study investigated whether Black adolescents' provision of different types of support to family (chores, childcare, emotional, financial support) was associated with their educational outcomes (school engagement, grades, suspensions), and whether these associations differed by household income levels. The study used the nationally representative National Survey of American Life Adolescent Supplement data ( N = 1170, 52% Female, ages of 13–17). Supporting the family was associated with both educational success and risk, depending on the type of support and household socioeconomic resource levels. Across income groups, providing emotional support was associated with greater school engagement. Among low‐income youth only, completei chores was associated with higher school engagement and grades, whereas providing childcare was associated with lower grades.